2004
DOI: 10.1111/j.0022-1112.2004.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Life history responses of fishes to culture

Abstract: The protected environment in culture permits fishes to reduce the proportion of energy normally channelled into the costs associated with competition for food, shelter and mates, avoidance of predators and counteracting parasites and diseases. The surplus energy so released is allocated to growth and reproduction, accelerating development through increased growth rate, earlier maturation and increased relative fecundity. Cultivators manipulate the rearing environment to remove seasonal variation in availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 140 publications
2
68
0
Order By: Relevance
“…The protected environment permits fish to allocate more energy to protein growth and lipid deposition, and several morphological changes occur in association with this (Thorpe, 2004). For example, cultured Atlantic salmon parr have smaller heads and rayed fins and narrower caudal peduncles than wild parr (Fleming et al, 1994).…”
Section: Changing Characteristics In Cultured Salmonmentioning
confidence: 99%
“…The protected environment permits fish to allocate more energy to protein growth and lipid deposition, and several morphological changes occur in association with this (Thorpe, 2004). For example, cultured Atlantic salmon parr have smaller heads and rayed fins and narrower caudal peduncles than wild parr (Fleming et al, 1994).…”
Section: Changing Characteristics In Cultured Salmonmentioning
confidence: 99%
“…Domestication processes and their management are increasingly well understood (Gross, 1998;Thorpe, 2004;Araki et al, 2008;Frankham, 2008). Many studies have been conducted to evaluate ecological differences between wild and released hatchery fish and their implications for population dynamics (Fleming and Petersson, 2001;Lorenzen, 2005).…”
Section: Key Developments Since the Responsible Approach Was First Fomentioning
confidence: 99%
“…When spawners are collected and stripped artificially, the intense competition on the spawning ground disappears. In nature, usually less than 5% of the eggs survive to the smolt stage (Jonsson et al 1998), while under hatchery conditions survival may be very high, with a corresponding change in selection (Piggins & Mills 1985;Thorpe 2004). Several studies have also revealed negative effects on wild populations from hatchery releases (reviewed by Araki & Schmid 2010).…”
Section: Planting Of Eggs From the Genebankmentioning
confidence: 99%